DEVELOPING A MEASURE OF LOCAL GOVERNMENTâS FINANCIAL CONDITION - Ritonga, Irwan Taufiq (Journal of Indonesian Economy and Business, 2014)
This study develops an instrument to measure the financial condition of local governments(LG) in Indonesia. The instrument will serve as an early warning system for local governmentsâfinancial management. The instrument to measure their financial condition consists of sixdimensions, namely short-term solvency, long-term solvency, budgetary solvency, service-levelsolvency, financial flexibility, and financial independence. Each dimension has its own indicators.There are a total of eighteen indicators examined in this study. These indicators are combinedto form a composite index, called a Financial Condition Index (FCI). The reliability andvalidity of the composite index is analyzed and the results show that the measures developed inthis study are reliable and valid. In addition, the instrument possesses the criteria of a goodmeasure: it is theoretically sound, a comprehensive assessment, it has predictive ability, distinctiveability, it is practical, objective, and a resistant to manipulation and gaming.Keywords: financial condition, local government, short term solvency, long term solvency,budgetary solvency, service-level solvency, financial flexibility, financial independence